DESENVOLVIMENTO DE FERRAMENTA PARA MAPEAR COMPETÊNCIAS GERENCIAIS: Estudo de Caso numa Empresa do Ramo Editorial - Lampoglia, Marco Antonio Luiz (2011)
Many organizations face the challenge of assuring their survival in fiercely competitive markets, consequently, the development of individual management competencies starts to be valued. The manager is in evidence before this scenario, performing relevant roles in the strategic process and in the organizational development. The mapping of management competences is part of an important search in the field of people management due to the fact that the diagnostics can t be transferred, automatically, from one organizational environment to another one. This dissertation had as its goal to develop a tool that maps the management competences and use this mapping in an editorial company. As part of this study five managers were interviewed in the same hierarchical level. The creation of this mapping contained descriptive analysis of auto and hetero perception as well as the difference between the two evaluation modalities. It is important to highlight that the study objective was able to be concluded, because the application of this tool allowed to identify aspects that need investments in management capacitation actions. It should be noted that this work is able to contribute with an initial base of knowledge for the reflection about the enterprise s strategic alignment according to expected behaviors correlated to each one of the twelve management competences identified during this study, as well as supporting new analysis and maps, creating also opportunities to an adequate implantation of training actions, with the intention of minimizing the risks of lack of the strategic alignment according to the responsibilities to be pursued by the managers in order to improve the result of the searched company.